2022
DOI: 10.3390/cells11091405
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Improved Understanding of the Effects of Elevated Progesterone Levels on Human Endometrial Receptivity and Oocyte/Embryo Quality during Assisted Reproductive Technologies

Abstract: Ovarian stimulation is an indispensable part of IVF and is employed to produce multiple ovarian follicles. In women who undergo ovarian stimulation with gonadotropins, supraphysiological levels of estradiol, as well as a premature rise in progesterone levels, can be seen on the day of hCG administration. These alterations in hormone levels are associated with reduced embryo implantation and pregnancy rates in IVF cycles with a fresh embryo transfer. This article aims to improve the reader’s understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 88 publications
2
11
0
Order By: Relevance
“…An imbalance of steroid hormones is related to many pregnancy complications, such as preeclampsia, caused by insufficient P4 [ 69 ]. A premature increase in P4 levels is related to abnormal implantation and decreased pregnancy rates [ 70 , 71 , 72 , 73 ]. Due to the paracrine effect of P4 on endometrial cells, the proliferation of endometrial cancer cells is inhibited [ 26 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance of steroid hormones is related to many pregnancy complications, such as preeclampsia, caused by insufficient P4 [ 69 ]. A premature increase in P4 levels is related to abnormal implantation and decreased pregnancy rates [ 70 , 71 , 72 , 73 ]. Due to the paracrine effect of P4 on endometrial cells, the proliferation of endometrial cancer cells is inhibited [ 26 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that members of the ADGR gene family are dynamically expressed across the natural menstrual cycle and early mouse pregnancy. Their expression also appears to be altered by ovarian stimulation, during which supraphysiologic levels of E2 and an early rise in P4 are seen (Kalakota et al 2022). The differential gene expression observed between the proliferative and secretory phase of the menstrual cycle, along with changes in expression seen with OS suggest that ADGR expression is hormonally regulated by E2 and P4.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian stimulation (OS), utilized for the development of multiple ovarian follicles for IVF, induces supraphysiologic levels of E2 and an early rise in P4 (Kalakota et al 2022). These hormonal changes induce morphological, biochemical, and functional genomic modifications that disrupt receptivity and decrease implantation rates following fresh embryo transfers (Kalakota et al 2022). Thus, with fresh embryo transfers, when the cultured embryo is returned to the uterine cavity, it may encounter a non-receptive endometrium, resulting in implantation failure.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most important sex steroids and key cyclical reproductive hormones with major impacts on the female organs of vertebrate species, progesterone (PRG) is mainly produced by the corpus luteum (CL) of the ovaries. Besides its reproductive significance, PRG can also be generated from the adrenal cortex, Leydig cells of the male testes, adipose cells and neuronal and glial cells [ 1 , 2 , 3 , 4 , 5 , 6 ], reaffirming its wide range of physiological effects, especially in the metabolic systems, central nervous systems and reproductive systems in both genders [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. PRG was first purified almost a century ago as an ovarian steroid with hormonal function for pregnancy [ 8 , 17 ].…”
Section: Introductionmentioning
confidence: 99%